Malignant Tumors of the Female Genital Tract – a Hospital Based Analysis - Joshi, R; Baral, G; Malla, K (Nepal Journal of Obstetrics and Gynaecology, 2016)
Aims: The incidence of cancer and the cancer related deaths are increasing worldwide. There is limited data regarding gynecological cancers in Nepal. This study is conducted to analyze the trends of female genital tract malignancies in Paropakar Maternity and Women’s Hospital (PMWH) and compare it with the national/international data. Methods: This was a retrospective study conducted in Department of Obstetrics/Gynecology and Pathology in PMWH. All female diagnosed with the genital tract malignancies from July 2013 to July 2015 were included in the study. Results: Among 62 cases, cervical cancer was the commonest (71%) followed by ovarian cancer (14%), endometrial cancer (8%) and choriocarcinoma (3%). Majority of women belonged to 50-59 years for each type of tumors. Four-fifth of endometrial, half of the cervical and one-third of ovarian cancers were among grand-multipara. Sixty nine percent of women received treatment with 22 (9 cervical, 9 ovarian, 3 endometrial and one of corpus uteri) surgical and 21 primary chemo/radiotherapy but 19 (31%) were lost for follow-up. Squamous type of cervical cancer was the commonest (93%). Conclusions: Cervical cancer was the commonest genital tract malignancy followed by ovarian cancer, endometrial cancer and choriocarcinoma. For each type of tumors, 50-59 years was the common age group and grand multiparity was seen in half of the women with the cervical cancer. Squamous type of cervical cancer was the commonest variety.